Characteristics of Marine Envenomation Cases in Kepulauan Seribu District Hospital, Indonesia - Hadiki Habib; Yogie Dwi Nugroho; Fitran Amansyah; Donny Alpha Edison; Ghamal Ahmad Pramana; Ma’mun -; Salinah - (Cermin Dunia Kedokteran, 2018)
Kepulauan Seribu district hospital frequently manage cases of marine envenomation. Recognizing characteristics of envenomation are needed to develop clinical guideline. Method. A cross sectional study during January to December 2016. Cases of marine envenomation in the Emergency Room of Kepulauan Seribu District Hospital, Jakarta, Indonesia were documented by structured medical records. Pictures of the affected body parts were also taken. Results. Sixteen cases of marine envenomation were documented. Most subjects (87,5%) were domestic tourists. The average age of the subjects were 21,12 years old. Pain is the most common chief complaint (81,3%). Most subjects seek medical treatment less than 2 hours after the incident (56,3%). Lionfish sting was the most common cause (50%) followed by jellyfish sting (25%), other causes were stingray, sea urchin, catfish and sea snake. Diagnosis were mostly made by focused anamnesis for animal identification (62,5%) and examination of the wounds (25%). Puncture type wound was the most common pattern (68,75%). Initial management by hot water immersion were only done in 56,3% cases. Conclusion. Lionfish sting was the most common cause of the envenomation cases in Kepulauan Seribu region. Identification of the animals and the wound patterns were the most common diagnostic methods. Hot water immersion was found to be effective to relief the pain but its use in medical management was not extensively applied. Rumahsakit daerah Kepulauan Seribu sering mengelola kasus-kasus medis sengatan binatang laut.Diperlukan data karakteristik kasus-kasus sengatan sebagai dasar pengembangan panduan pelayanan medis. Metode. Studi cross-sectional dari Januari-Desember 2016. Kasus-kasus sengatan binatang laut yang dating ke Instalasi Gawat Darurat (IGD) Rumah Sakit Kepulauan Seribu dicatat dalam rekam medis terstruktur, bagian tubuh yang terkena sengatan juga difoto. Hasil,Terdapat 16 kasus sengatan binatang laut yang dicatat. Sebagian besar (87,5%) wisatawan domestik. Rerata usia pasien 21,12 tahun. Nyeri adalah keluhan utama terbanyak, 56,3% pasien mendatangi rumah sakit kurang dari 2 jam setelah sengatan. Ikan lepu adalah penyebab sengatan tersering (50%), diikuti sengatan ubur-ubur (25%), hewan penyebab lain adalah ikan pari, bulu babi, ikan sembilang, dan ular laut. Diagnosis berdasarkan informasi hewan yang teridentifikasi sebagai penyebab, (62,5%) atau melalui pemeriksaan pola luka (25%). Luka tusukan adalah yang paling sering (68,75%). Pertolongan awal dengan rendaman air hangat hanya dilakukan pada 56,3% kasus. Simpulan : Ikan lepu adalah penyebab sengatan binatang tersering di daerah Kepulauan Seribu. Identifikasi hewan penyebab dan pola luka adalah metode penegakan diagnosis yang paling sering. Rendaman air hangat efektif mengatasi rasa nyeri namun belum lazim dilakukan.